Konsep Pendekatan Behavior dalam Menangani Perilaku Indisipliner pada Siswa Korban Perceraian (Jurusan Bimbingan dan Konseling Islam, 2018)
This article approaches the concept memapakan behavior in dealing with student behavior insdisipliner the victims of divorce. Behavior itself is one wide approach in guidance and counseling to address maladaptife toward adaptive behavior. Behavior approach is the right approach to deal with students who are not disciplined in school. That the students be able to function well in school, without obstacles. Undisciplined behavior is influenced by one factor, namely the problems of internal students of SMP Diponegoro Depok, Sleman, Yogyakarta, which tend to be on the student's background as a result of divorce. The research method using descriptive qualitative endekatan with emphasis on spaciousness directly involved. Furthermore, if the assessment has been carried out, the plan can be implemented into the counseling process. Starting contracts counseling, relaxation, modeling, reward and punisment until the follow-up phase. By this stage of the process of changing the flow behavior of students who are not disciplined attitude can be reduced. And students are able to be adaptive.